2010
DOI: 10.4209/aaqr.2010.04.0031
|View full text |Cite
|
Sign up to set email alerts
|

The Indoor and Outdoor Carbonaceous Pollution during Winter and Summer in Rural Areas of Shaanxi, China

Abstract: ABSTRACT, and 7.4 µg/m 3 , respectively). The average indoor/outdoor (I/O) ratios for PM 2.5 and EC were close to or less than 1.0 and those for OC and BC were above 1.0. The correlation coefficients of PM 2.5 and carbon species also indicated that the indoor concentrations of PM 2.5 and carbonaceous aerosol were correlated with the corresponding outdoor concentrations. Average OC/EC ratios ranged from 4.6 to 23.6 with an average of 9.1 during winter and from 4.2 to 12.0 with an average of 6.3 during summer. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 44 publications
1
14
0
Order By: Relevance
“…The mechanisms for the cardiovascular effects are not completely understood, but a possible hypothesis is that, because of their small size, UFPs could enter the systemic circulation and induce direct effects on myocardium or coronary vasculature (Nemmar et al, 2004). Several studies have indicated that about 50-70% of UFP mass consists of carbonaceous material (Puxbaum and Wopenka, 1984;Berner et al, 1996;Hughes et al, 1998;Chen et al, 2010;Zhu et al, 2010b). Combustion-derived ultrafine particles, such as diesel soot, are the most numerous particles, by number, in urban PM 10 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The mechanisms for the cardiovascular effects are not completely understood, but a possible hypothesis is that, because of their small size, UFPs could enter the systemic circulation and induce direct effects on myocardium or coronary vasculature (Nemmar et al, 2004). Several studies have indicated that about 50-70% of UFP mass consists of carbonaceous material (Puxbaum and Wopenka, 1984;Berner et al, 1996;Hughes et al, 1998;Chen et al, 2010;Zhu et al, 2010b). Combustion-derived ultrafine particles, such as diesel soot, are the most numerous particles, by number, in urban PM 10 .…”
Section: Introductionmentioning
confidence: 99%
“…TC particles act as carriers of toxic compounds inside the human respiratory system causing Chronic Obstructive Respiratory Diseases (CORDs) and/or new pathologies related with the pollutants delivered (Avino et al, 2004). In recent years several worldwide studies on aerosol particle number concentrations and size distribution have been published (Hussein et al, 2003;Buonanno et al, 2009;Buonanno et al, 2010;Chen et al, 2010;Liu et al, 2010;Zhu et al, 2010b). Because of lack of relevant data in the urban area of Rome, a study has been undertaken on UFP number size distribution and composition, starting from measuring carbonaceous particulate matter.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The IMPROVE_A protocol (Zhu et al, 2010;Chow et al, 2011) produces four OC fractions (OC1, OC2, OC3, and OC4 in a helium (He) atmosphere at 140°C, 280°C, 480°C, and 580°C, respectively), a pyrolyzed carbon fraction (OP, determined when reflected laser light attained its original intensity after oxygen (O 2 ) was added to the combustion atmosphere); and three EC fractions (EC1, EC2, and EC3 in a 2% oxygen/ 98% helium atmosphere at 580°C, 740°C, and 840°C, respectively). OC is defined as OC1 + OC2 + OC3 + OC4 + OP and EC as EC1 + EC2 + EC3 -OP.…”
Section: Methodsmentioning
confidence: 99%
“…Numerous papers are found in the literature (Zhu et al, 2010;Masih et al, 2012;Zhu et al, 2012). In general, particles less than 2.5 micrometers in diameter are called "fine particles" or PM 2.5 (PM with aerodynamic diameters < 2.5 μm).…”
Section: Introductionmentioning
confidence: 99%